Deciphering mechanical cues in the microenvironment: from non-malignant settings to tumor progression - Yicheng Zhu; Jiaoshun Chen; Chen Chen; Rong Tang; Jin Xu; Si Shi; Xianjun Yu (Biomarker Research)
Highlight Distinct mechanical cues in the tumor microenvironment drive tumor behaviors and highlight potential therapeutic targets.